Reconstructing Corporate Environmental Sanctions through Ecological Justice in Indonesia - Saritua Silitonga; Anggiat p. Simamora; Surya Hamdani; Sarah Furgoni (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Corporate environmental crime in Indonesia raises a difficult socio-legal problem: sanctions may punish polluting corporations while damaged ecosystems remain unrestored. This article examines how sanctions against corporate polluters are constructed under Indonesian law and how they should be reconstructed in light of ecological justice. The study uses normative legal research with socio-legal sensitivity, applying statutory, conceptual, and prescriptive approaches to legislation, corporate liability doctrine, environmental sanction provisions, and the ecological justice literature. The findings show that Indonesian law recognises corporate criminal liability and additional sanctions, including restoration, profit confiscation, closure of business activities, fulfilment of neglected obligations, and corporate supervision. However, the framework is weakened by discretionary restoration orders, evidentiary difficulty, institutional fragmentation, and an anthropocentric legal culture. The article contributes a restoration-oriented reconstruction model that places ecological recovery, unlawful gain removal, corporate compliance reform, and executable institutional mechanisms at the centre of environmental punishment. It argues that sanctions should be assessed not merely by their punitive severity, but by their capacity to repair ecological harm and prevent recurrence.